OPTIMASI DOSIS PUPUK N, P, DAN K TERHADAP PERTUMBUHAN VEGETATIF AWAL TANAMAN PARIA (Momordica charantia L.) DI MEDIA POLIBAG - Rizva, Dian Novira; Munawaroh, Siti; Zuhra, Nur Halimatuz; Dary, Raihan; Br Surbakti, Dian Permata Sari (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2026)
This study aims to determine the optimum dosage of Nitrogen (N), Phosphorus (P), and Potassium (K) fertilizers to support the growth of Bitter Gourd (Momordica charantia L.). The experiment was conducted using a single-factor Completely Randomized Design (CRD), consisting of fertilizer dosage levels at 0%, 25%, 50%, and 75% of the recommended doses (equivalent to 5 g Urea, 4 g SP-36, and 4 g KCl per plant). Observations were made on plant height at 1 and 2 weeks after planting (WAP), number of leaves at 1 and 2 WAP, as well as fresh weight and dry weight. The results indicated that variations in N, P, and K fertilizers dosages significantly influenced all growth parameters. Generally, the treatment at 25% of the recommended dose showed the best results compared to other treatments. Quadratic regression analysis revealed that the optimum dosages for plant height at 1 WAP and 2 WAP were 25.71% (R² = 0.64) and 19.70% (R² = 0.53) of the recommended dose, respectively. The optimum dosage for number of leaves at 2 WAP was 15% (R² = 0.50), while the optimum dosages for fresh weight and dry weight were 8.5% (R² = 0.56) dan 10.38% (R² = 0.55) respectively.